The Political Ethical Considerations and Artificial Intelligence: The Political Ethical Considerations and Artificial Intelligence - Phramaha Chatchai Punyawattano (Polsri); Phongtong, Ittipol; Tho-un, Worachet (RATANABUTH JOURNAL, 2023)
This article aims to reflect on the capabilities of AI innovation in shaping and revolutionizing the political landscape and election processes in democratic societies. It can predict election outcomes by analyzing data from opinion surveys, social media trends, and past voting patterns. Additionally, it utilizes AI-driven chatbot systems to engage with voters, gather information about candidates, policies, and polling locations, and analyze political sentiments to identify key issues, sentiments, and emotional triggers that connect with the audience. AI also offers policy recommendations based on public opinion data, enhancing the effectiveness of political advertising campaigns, fact-checking political campaigns, and analyzing social media and news sentiment in real-time to gauge public opinions. Furthermore, the potential of AI systems for autonomous learning and development can lead to unforeseen outcomes, as witnessed in cases where AI developed its own language or exhibited biased behavior. To mitigate these concerns, it is crucial to establish ethical guidelines and regulations for the responsible use of AI in a destructive manner. Transparency in AI development, testing, and implementation is essential to ensure accountability and prevent misuse. Developing AI with responsibility in mind should prioritize human oversight and control to ensure that AI systems are used as decision-making tools rather than replacements for human judgment.